2015
DOI: 10.1155/2015/842032
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality Pattern in Lagos University Teaching Hospital, Lagos, Nigeria

Abstract: Background. Cancer is a leading cause of death worldwide and about 70% of all cancer deaths occurred in low- and middle-income countries. The cancer mortality pattern is quite different in Africa compared to other parts of the world. Extensive literature research showed little or no information about the overall deaths attributable to cancer in Nigeria. Aims and Objectives. This study aims at providing data on the patterns of cancer deaths in our center using the hospital and autopsy death registers. Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 15 publications
7
37
2
Order By: Relevance
“…Our findings demonstrate a substantial burden of cancer patients in Ghana requiring general surgery admission. Similar to other reports in the literature from SSA, the most common cancer types seen here were breast, colorectal, and foregut . Majority of all admitted patients went on to undergo surgery (208, 61%) which is slightly higher than rates previously reported from Rwanda, where 46% of patients presenting for surgical evaluation underwent an operation .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings demonstrate a substantial burden of cancer patients in Ghana requiring general surgery admission. Similar to other reports in the literature from SSA, the most common cancer types seen here were breast, colorectal, and foregut . Majority of all admitted patients went on to undergo surgery (208, 61%) which is slightly higher than rates previously reported from Rwanda, where 46% of patients presenting for surgical evaluation underwent an operation .…”
Section: Discussionsupporting
confidence: 85%
“…Similar to other reports in the literature from SSA, the most common cancer types seen here were breast, colorectal, and foregut. [21][22][23] Majority of all admitted patients went on to undergo surgery (208, 61%) which is slightly higher than rates previously reported from Rwanda, where 46% of patients presenting for surgical evaluation underwent an operation. 24 In addition, most patients in our study who underwent surgery did so with curative intent (124, 60%…”
Section: Discussionmentioning
confidence: 64%
“…Over the past two decades, there has been a remarkable increase in the incidence of breast cancer from 33.6 per 100,000 in the 1990s to 64.6 per 100,000 after about two decades making breast cancer the most common female malignancy in Nigeria (Adebamowo & Adekunle, ; Jedy‐Agba et al, ). The majority of women present with advanced disease (Adesunkanmi, Lawal, Adelusola, & Durosimi, ), making breast cancer one of the leading causes of cancer death (Akinde, Phillips, Oguntunde, & Afolayan, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is the most prevalent cancer in Nigeria and the commonest cause of cancer-related deaths in some Nigerian regions such as Lagos [1,2]. The age-standardised incidence rate in Nigeria is 34-46 per 100,000, and some studies have reported an increasing incidence in recent years [1,3].…”
Section: Introductionmentioning
confidence: 99%